Rekayasa Matarial Akustik Ruang Dalam Desain Bangunan : Studi Kasus Rumah Tinggal Sekitar Bandara Adisutjipto Yogyakarta - K Kaharuddin; Arif Kusumawanto (Faculty of Engineering, Universitas Gadjah Mada, 2011)
This research was conducted to determine the conditions and manipulate the acoustic material by the mathematical experiment method the calculations was using a specific formula replacing the value of material acoustic sound coefficient. The focus of this research was analyzing the sound absorption and noise reductions of acoustic materials used in residential arround Adisutjipto airport of Yogyakarta then proceed with the analysis of sound absorption and noise reduction of coconut palm fiber designed acoustic materials based on buiding physical theory.The results show that the low sound absorption and noise reduction of the acoustic material inside the sample chamber was due to the material used had a sound reflector characteristic, so optimize the noise reduction it was needed an additional layer of acoustic material used in the fields. The high sound absorption and noise reduction of the coconut palm fiber desgned materials caused by these materials had sound-absorbing properties. The addition of coconut palm fiber layer for acoustic material could optimize the noise reduction. In addition, the coconut palm fiber acoustic material could be used as an altenative sound dampening material at high frequencies that could potentially reduce the waste of nature. Keywords : Residential, accustics materials, coconut fiber, mathematical experiment.